MULTICULTURAL PRAGMATICS: CONVERSATIONAL IMPLICATURE IN SELLER-CONSUMER INTERACTION PADANG, INDONESIA - Fhitri, Widya; Yalmiadi, Yalmiadi; Medina, Samantha (Journal of Pragmatics and Discourse Research, 2025)
This study explores the use of conversational implicature in seller-consumer interactions at cellular phone shops in Padang, Indonesia. It emphasizes how vendors employ implicit communication techniques to subtly communicate ideas, conform to cultural standards, and sway consumer choices. The study aims to comprehend how these nuanced language strategies support salespeople in establishing rapport, offering product details, and eventually achieving favorable sales results. By examining how well various tactics work, the study highlights how crucial culturally sensitive communication is to raising customer satisfaction and trust. Demonstrating the usefulness of language in transactional contexts advances the discipline of pragmatics. Leveraging Yule’s and Searle’s pragmatic frameworks, the research examines the types and functions of implicatures in these conversations. Using an observational qualitative method, data were collected through recording and note-taking techniques at three prominent locations in Padang. The findings reveal that conversational implicature is the most frequently used type, enabling sellers to subtly convey product information and build rapport without being overly direct. Representative functions dominate, as sellers provide product details and emphasize advantages. Commissive functions, such as promises of after-sales service, and expressive functions, aimed at rapport-building, are also prevalent. This study highlights the socio-cultural underpinnings of transactional communication, demonstrating how implicature aligns with local norms of indirectness in casual exchanges. The findings have practical implications for improving sales strategies, emphasizing the role of nuanced communication in consumer trust-building. This research contributes to the field of pragmatics by elucidating the role of language in shaping buyer perceptions and decision-making. Future studies could further explore the impact of implicature across different cultural and retail contexts to enhance cross-cultural consumer communication.